THE SITUATION OF THE FRANCOPHONIE AND THE FRANCOPHONE CULTURE IN KOSOVO - Luma Krenare (Association of Social and Educational Innovation, 2020)
The educational and sociolinguistic context in post-war Kosovo and the cooperation in building a current educational system have gone through very specific histories. The current situation of French and Francophonie is the result of great changes throughout history. All this sociolinguistic situation is closely related to the sociopolitical context.Any linguistic situation is necessarily linked to the socio-political context, but in Kosovo more than elsewhere. It must be remembered that, for ten years, the Serbian judiciary had a long arm and that one in two Albanian-speaking adults had already been arrested in one way or another by the police. The massacres resulting from the violence had become part of everyday life. In 1999, during the Kosovo War, Serbian revenge experienced unprecedented developments while ethnic cleansing in Albania accelerated rapidly during 1998-1999. At present, the official languages of Kosovo are Albanian and Serbian. At the municipal level, minority languages such as Turkish, Bosnian and Romani are languages officially used under specific conditions.French is only the language of communication between French-speaking communities and French-speaking Kosovars working in contact with embassies and cultural services in French-speaking countries. In this context French therefore has the status of a foreign language in its own right. It is also taught as a second foreign language in schools in the same way as German.